Software for systematization of nursing care in medical units - Manoel Gomes da Silva Junior; Eliete da Cunha Araújo; Carlos Ramon Silva Moraes; Lucia Hisako Takase Gonçalves
ABSTRACT Objective: To describe the development of a software prototype to apply the nursing process in clinical units of a general hospital, and assess its usefulness. Method: Applied methodological research of technological production of a program based on prototyping software engineering developed in three stages: specification, development, and validation. Results: Produced under the name of INFOSAE, the system represents a set of stages (history, diagnosis, expected outcomes, and nursing intervention) providing guidance to nurses to direct and guarantee the necessary care to patients, also allowing an assessment of this care. Conclusion: The INFOSAE software prototype, an easy-to-use computerized technology, obtained a favorable assessment by the user nurses that participated in the whole development process, from the specification to the validation of the system.